1998
DOI: 10.1103/physrevlett.80.1869
|View full text |Cite
|
Sign up to set email alerts
|

Giant Spin Relaxation of an Ultracold Cesium Gas

Abstract: We have measured the rate of inelastic collisions in a cloud of doubly polarized ground-state cesium atoms (F m F 4) confined in a magnetic trap for temperatures T between 8 and 70 mK. We find a two-body rate coefficient varying as T 20.63 . At 8mK it reaches 4 3 10 212 cm 3 s 21 which is 3 orders of magnitude larger than predicted, ruling out a Bose-Einstein condensation of Cs in this internal state.[ S0031-9007(98) [3] has attracted a lot of attention. The atomic sample is spin polarized and confined in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
94
2

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(102 citation statements)
references
References 16 publications
6
94
2
Order By: Relevance
“…Large inelastic losses that grow as the temperature is reduced were discovered that prevent the condensation of cesium in this state [25][26][27].…”
Section: Inelastic Feshbach Spectroscopymentioning
confidence: 99%
“…Large inelastic losses that grow as the temperature is reduced were discovered that prevent the condensation of cesium in this state [25][26][27].…”
Section: Inelastic Feshbach Spectroscopymentioning
confidence: 99%
“…For all isotope combinations, we find that heteronuclear thermal relaxation is outbalanced by intrinsic heating caused by ionizing collisions: Since ionizing collisions occur preferentially at the center of the trap, where the density is highest and the energy of the atoms is lowest, these collisions remove atoms with below average energy. This leads to an effective heating of the remaining atoms (see also [21,26]). The heating rate per ionizing collision depends on the mean energy E C carried away by the collision products relative to the mean energy E T of all atoms in the trap.…”
Section: Heteronuclear Elastic Collisionsmentioning
confidence: 99%
“…The heating rate per ionizing collision depends on the mean energy E C carried away by the collision products relative to the mean energy E T of all atoms in the trap. The heating rate is given by [26] …”
Section: Heteronuclear Elastic Collisionsmentioning
confidence: 99%
“…Moreover, investigations in both ultracold gases [24] and optically pumped vapor cells [25] have revealed that even for heavy alkali-metal collisions the hierarchy γ c ≈ γ SE ≫ γ SR is fulfilled. In such a situation, the dominant spin-exchange interaction leads to a steady state near a perfect polarization of spin and environment both when the environment is initially polarized but the spin is unpolarized and when the single spin is continuously pumped but the environment is initially unpolarized.…”
mentioning
confidence: 99%